Principles of the Olympic Movement - Durantez, C.; Turpin, J. P.; Vidal, A. M.; Padorno, C. M.; Patino, M. J. M.; Molina, A. G. (Journal of Human Sport & Exercise, 2010)
The aim of this article is to clarify, review and reflect on the importance of the Olympic movement main principles on nowadays sporting society. For this purpose, the paper goes through the contents of the Olympic Charter, the threats to humanist thinking, the Olympic Games history and the most recent contributions to the Olympic philosophy. Similarly, this article goes deep on the figure of Pierre de Coubertin as the precursor of modern Olympic Games leading to the development of a relationship between the Olympic phenomenon and the need to establish an ethic conduct that embraces all the sports grandeur. Thus, the contribution of this Olympic education is used, through its principles of peace, personal development, equality and ecology in the next generations to come.